Combined Application of Regenerative Combustion Technology and Porous Medium Combustion Technology. (2015) - Shi, Weihua; Wang, Dongfan
Abstract: This paper discusses that the combined technology of regenerative combustion technology and porous medium combustion technology is used to achieve the steady combustion of low calorific value fuel and to realize solution. Research shows that using the combined new combustion technology of regenerative combustion technology and porous medium combustion technology can achieve the effective, safe, energy saving and low pollutant emission of low calorific value fuel and can also have a positive environmental protection effect and social benefits.